Treatment of maxillary central incisors with internal resorption: Two case reports - TÜRKAYDIN, DİLEK; İRİBOZ, EMRE; SAZAK ÖVEÇOĞLU, HESNA (My University, 2019)
Internal root resorption is a rare condition, but it may require complex treatment protocols, depending on the progression. The aim of this case report is to present the treatment protocol and the follow-up results for 2 cases of a right upper central incisor with internal root resorption. A 15-year-old female patient presented with the chief complaint of dental caries. The radiological examination revealed that tooth #21 had internal resorption (IR) in the middle third of the root. The warm vertical condensation technique was applied using a warm obturation system. At 3 years, the tooth was asymptomatic and no lesions were observed. A 48-year-old female patient was referred to the clinic for a routine control. The radiological examination revealed IR in the middle third of tooth #21. As the resorption area was quite wide, cone beam computed tomography was used. The results indicated that there was also external resorption in the buccal part of the root. Therefore, the treatment protocol was changed and the IR area was sealed with mineral trioxide aggregate. At 1 year, the tooth was asymptomatic and no lesions were observed. Keywords: Cone beam computed tomography; internal root resorption; mineral trioxide aggregate; root perforation; trauma.
Keywords: Sağlık Bilimleri; Diş Hekimliği; Klinik Bilimler; Endodonti; Health Sciences; Dentistry; Clinical Sciences; Endodontics; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry; Cone beam computed tomography; internal root resorption; mineral trioxide aggregate; root perforation; trauma